2017
DOI: 10.1097/tp.0000000000001605
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Direct-Acting Antiviral Treatment in Hepatitis C–Infected Liver Transplant Candidates With Compensated Cirrhosis and Hepatocellular Carcinoma

Abstract: Background HCV(+) donors represent an effective strategy to increase liver donor availability to HCV-infected recipients. However, many HCV(+) transplant candidates are now receiving treatment with direct acting anti-virals (DAA) that lower the risk of posttransplant HCV recurrence but could make the patient ineligible for HCV(+) livers. Methods We compared pretransplant DAA treatment versus deferred DAA treatment using a cost-effectiveness decision analysis model to estimate incremental cost-effectiveness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…There are exceptions in liver disease cohorts. Patients with hepatocellular carcinoma and relatively low Model for End‐Stage Liver Disease (MELD) scores did better with deferred therapy with the option of receiving an HCV viremic organ earlier . Although not modeled specifically, kidney disease patients with significant residual function not yet on dialysis should have reduced rates of progression to ESRD with DAA treatment and may potentially benefit more from early intervention …”
Section: Discussionmentioning
confidence: 99%
“…There are exceptions in liver disease cohorts. Patients with hepatocellular carcinoma and relatively low Model for End‐Stage Liver Disease (MELD) scores did better with deferred therapy with the option of receiving an HCV viremic organ earlier . Although not modeled specifically, kidney disease patients with significant residual function not yet on dialysis should have reduced rates of progression to ESRD with DAA treatment and may potentially benefit more from early intervention …”
Section: Discussionmentioning
confidence: 99%
“…Deferring HCV treatment until after LT in order to guarantee access to the expanded pool of HCV-positive donors has been proposed as the most cost-effective strategy for well-compensated HCV-infected patients with cirrhosis listed for LT with HCC. (44) However, this still depends on HCV epidemiology. Furthermore, HCV eradication in the pre-LT setting prevents recurrence of liver infection (45) and has been associated with higher survival in patients transplanted for HCC.…”
Section: Included 1 Cohort Of Hcc Lt Recipients Subsequently Treated mentioning
confidence: 99%
“…In this context, HCC should be controlled with LRT first before treating HCV with DAAs, and this may result in disease stabilization and even reduction in liver‐related death on the waiting list. The decision regarding DAA treatment before versus after LT is complex, but it should take into account the degree of hepatic decompensation and availability of regional HCV‐positive donor livers …”
Section: Daas and The Threat Of Hcc: Where Is The Evidence?mentioning
confidence: 99%
“…The decision regarding DAA treatment before versus after LT is complex, but it should take into account the degree of hepatic decompensation and availability of regional HCV-positive donor livers. (28) For LT recipients for HCC who received DAAs, data assessing the impact of DAAs on the risk of HCC recurrence after LT are scant. Yang et al (29) reported a 27% (5/18) HCC recurrence rate after DAA therapy followed by LT versus 9.5% (6/63; P 5 0.06) in those who did not receive DAAs prior to LT.…”
Section: Daas and Hcc Recurrence After Resection Or Lrtmentioning
confidence: 99%